VNTR Polymorphism in Intron 4 of the eNOS Gene and the Risk of Gastrointestinal Bleeding: A Case-control Study - Forgerini, Marcela [UNESP]; Urbano, Gustavo; de Nadai, Tales Rubens; Zanelli, Cleslei Fernando [UNESP]; Valentini, Sandro Roberto [UNESP]; Mastroianni, Patrícia de Carvalho [UNESP] (Romanian Society of Gastroenterology and Hepatology, 2022)
Background & Aims: Considering the lack of knowledge regarding the influence of the variable number of repeats of 27 pb in intron 4 (4b/4a VNTR-rs61722009) of the endothelial nitric oxide synthase (eNOS) on the drug response, we assessed the influence of this polymorphism for the risk of upper gastrointestinal bleeding (UGIB). Methods: A case-control study, including 200 cases and 706 controls, was conducted in a Brazilian hospital complex. Cases were participants with UGIB diagnosis. Controls were participants admitted to surgical procedures not related to gastrointestinal problems. The 4b/4a VNTR was determined through polymerase chain reaction followed by fragment analysis. Conditional logistic regression models were designed. The additive interaction between the presence of the 4b/4a VNTR variant and the use of low-dose aspirin (LDA) and nonsteroidal anti-inflammatory drugs (NSAIDs) was calculated by fitting the Cox regression model through the parameters of Synergism index (S) and Relative Excess Risk Due To Interaction (RERI). Results: The presence of the 4b/4a VNTR variant did not increase the risk of UGIB: carriers of the 4a/4a genotype (OR=0.37, 95%CI: 0.09-1.45) and of the variant allele “4a” (OR=0.91, 95%CI: 0.55-1.51). The risk of UGIB in LDA users carriers of the wild genotype (OR=4.96, 95%CI: 2.04-2.06) and the variant allele “4a” (OR=3.49, 95%CI: 1.18-10.38) is similar, as well as for NSAID users carriers of the wild genotype (OR=5.73, 95%CI: 2.61-12.60) and variant allele “4a” (OR=5.51, 95%CI: 1.42-15.82). No additive interaction was identified between the presence of the genetic variant and the use of LDA [RERI:-1.44 (95%CI:-6.02–3.14; S: 0.63 (95%CI:-1.97–1.15)] and NSAIDs [RERI:-0.13 (95%CI:-6.79–6.53; S: 0.97 (95%CI:-0.23–4.19)] on the UGIB risk. Conclusion: Our data suggests that there is no increase in the magnitude of UGIB risk in LDA and NSAIDs users’ carrying the variant allele “4a”.
Keywords: aspirin; gastrointestinal bleeding; nonsteroidal anti-inflammatory drugs; NSAIDs; peptic ulcer hemorrhage; tandem repeat sequences; UGIB; VNTR Sequences